Multi-layer continuous carbon fiber pattern optimization and a spline based path planning interpretation - Wein, Fabian; Mirbach, Julian; Angre, Aniket; Greifenstein, Jannis; Hübner, Daniel (Journal of Manufacturing Processes, 2025)
A novel approach for creating tool paths for continuous carbon fiber-reinforced thermoplastic 3D printing is introduced. The aim is to enable load-bearing connections and realize crossings of fibers by generating layer specific patterns. As input we use a graph representation of the structural design with given desired continuous fiber connections. From this, optimal fiber patterns are obtained for each printing layer by solving linear integer optimization problems. Each layer may have a unique solution based on the history of the previous layers. Additionally, a path planning approach is presented which interprets the obtained layers via curves based on quadratic and cubic Bézier splines and their offset curves in constant distance. The single parameter for the construction of the paths is the minimal turning radius of the fibers. The path planning provides a new interpretation for the final geometry of the design to be printed. With the novel approach presented, for a given design, continuous print paths are automatically generated across multiple print layers, respecting manufacturing constraints (parallel paths, minimum turning radius, no crossings), with the goal of achieving the best mechanical properties. This is an important tool to generate printing machine control from a given design description to print high performance parts. The multilayer patterns are a significant improvement over conventional single-layer print path layout methods.
CRIS-Team Scopus Importer:2025-01-31
Keywords: 3D printing; C-CFRTP; CFRP